The impacts of oil palm plantation establishment on the habitat type, species diversity, and feeding guild of mammals and herpetofauna - ROZZA TRI KWATRINA; YANTO SANTOSA; M. BISMARK; NYOTO SANTOSO (Biodiversitas Journal of Biological Diversity, 2018)
Kwatrina RT, Santosa Y, Bismark M, Santoso N. 2018. The impacts of oil palm plantation establishment on the habitat type, species diversity, and feeding guild of mammals and herpetofauna. Biodiversitas 19: 1213-1219. Indonesia is the world’s largest producer of palm oil. Contributing 2.14% to the country’s gross domestic product, palm oil plays an important role in the national economy from plantation sector. However, the expansion of oil palm plantations has brought negative impacts to forests and wildlife. Little is known to what extent these negative impacts on mammals and reptiles can be reduced through better management. To address this knowledge gap, the current study assessed species diversity as affected by the establishment of the oil palm plantation in Central Kalimantan, a tropical biodiversity hotspot in Asia. We conducted 25 line transect surveys and visual encounter surveys in oil palm areas, shrubs and secondary forests in these landscapes. The results indicated that the establishment of oil palm plantation negatively impacted species abundance and diversity, and changed the mammal and reptile species composition, by favoring ecologically generalist species. For forest specialist species, forested areas like HCV and HCS, play an important role in maintaining habitat heterogeneity in oil palm landscapes. Mammal species found in habitat conditions following oil palm plantations belong to some feeding groups, whereas all species of herpetofauna have terrestrial habitat types. These mammal and herpetofauna species can live and function in the food chain in the oil palm plantation ecosystem.